Curcumin Attenuates Acrolein-induced COX-2 Expression and Prostaglandin Production in Human Umbilical Vein Endothelial Cells - Lee, Seung Eun (J Lipid Atheroscler, 2020)
OBJECTIVE: Inflammation is crucial to limiting vascular disease. Previously we reported that acrolein, a known toxin in tobacco smoke, might play an important role in the progression of atherosclerosis via an inflammatory response involving cyclooxygenase-2 (COX-2) and prostaglandin production in human umbilical vein endothelial cells (HUVECs). Curcumin has been known to improve vascular function and have anti-inflammatory properties. In this study, we investigated whether curcumin prevents the induction of inflammatory response caused by acrolein. METHODS: Anti-inflammatory effects of curcumin were examined in acrolein-stimulated HUVECs. Induction of proteins, mRNA, prostaglandin and reactive oxygen species (ROS) were measured using immunoblot analysis, real-time reverse-transcription polymerase chain reaction, enzyme-linked immunosorbent assay and flow cytometry, respectively. RESULTS: Curcumin attenuates inflammatory response via inhibition of COX-2 expression and prostaglandin production in acrolein-induced human endothelial cells. This inhibition by curcumin results in the abolition of phosphorylation of protein kinase C, p38 mitogen-activated protein kinase, and cAMP response element-binding protein. Furthermore, curcumin suppresses the production of ROS and endoplasmic reticulum stress via phosphorylation of eukaryotic initiation factor-2α caused by acrolein. CONCLUSION: These results suggest that curcumin might be a useful agent against endothelial dysfunction caused by acrolein-induced inflammatory response.